2017
DOI: 10.4274/jcrpe.3794
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Disordered Eating Attitudes with Stress Level, Bone Turnover Markers, and Bone Mineral Density in Obese Adolescents

Abstract: Objective:To investigate the effect of stress caused by disordered eating attitudes on bone health in obese adolescents.Methods:A cross-sectional study comprising 80 obese adolescents was performed from November 2013 to September 2014. Twenty-four-hour urinary free cortisol levels were measured as a biological marker of stress. Bone turnover was evaluated using bone-specific alkaline phosphatase, serum osteocalcin, and urinary N-telopeptide concentrations. Bone mineral density was measured using dual-energy X-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…BMD is afected by many factors during the teenage years, and genetic factors account for 60-80% of BMD [26]. In addition, the hormonal milieu and individual and environmental modifable factors, such as body weight, obesity, diet, and physical activity, also play an important role in BMD later in life [27,28]. Terefore, the reason for this inconsistency cannot be simply attributed to a specifc reason, and further research is needed.…”
Section: Discussionmentioning
confidence: 99%
“…BMD is afected by many factors during the teenage years, and genetic factors account for 60-80% of BMD [26]. In addition, the hormonal milieu and individual and environmental modifable factors, such as body weight, obesity, diet, and physical activity, also play an important role in BMD later in life [27,28]. Terefore, the reason for this inconsistency cannot be simply attributed to a specifc reason, and further research is needed.…”
Section: Discussionmentioning
confidence: 99%
“…Counting colors rather than calories may be a more effective way to engage long-term lifestyle change, although that concept has yet to be tested. Using this simplified approach to food may also help the category of restrained eaters, who tend to have low self-esteem [ 179 ], higher stress [ 180 ], and disordered eating patterns compared with nonrestrained eaters.…”
Section: Practical Ways To Get More Colorful Fruits and Vegetablesmentioning
confidence: 99%
“…In the literature, it was shown that there is a relation-ship between depression and obesity (4)(5)(6)(7)(8) . Both depression and obesity were reported to be associated with an increase in cardiometabolic risk factors both in adolescents and adults (3,9,10) .…”
Section: Discussionmentioning
confidence: 99%
“…Between January 2012 to December 2015, four different studies with overweight/obese adolescents were conducted in our clinic. For this study, the cases in those four studies were retrospectively screened and those evaluated with Children's Depression Inventory (CDI) were included in this study (8,(11)(12)(13) . Pubertal patients who met the criteria for definition of overweightness/obesity established by Cole et al (14) according to age and gender and had been evaluated with CDI were included in this study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation